LATE-GLACIAL AND EARLY HOLOCENE VARIATIONS IN ATMOSPHERIC CO2 CONCENTRATION INDICATED BY HIGH-RESOLUTION STOMATAL INDEX DATA - Rundgren M.; Björck S. (My University, 2003)
Data from ice cores suggest that Late-glacial and early Holocene atmospheric CO2 variations were rather conservative, the most important change being a gradual Younger Dryas increase. By contrast, palaeo-CO2 records based on the inverse relationship between CO2 partial pressure and stomatal frequency of terrestrial plant leaves reflect a more dynamic CO2 evolution, including an abrupt decrease at the Allerød/Younger Dryas transition. Here we present a Late-glacial and early Holocene CO2 record based on stomatal index data from leaves preserved in the sediments of a small lake in southwestern Sweden. Three independent records constructed from stomatal index data of Salix polaris, Salix herbacea and Betula nana leaves were combined to form a high-resolution CO2 reconstruction for the period 12 800–10 800 cal yr BP. Atmospheric CO2 concentrations were found to have decreased rapidly from c. 260 ppmv to 210–215 ppmv within 200 years during the Allerød (GI-1)/Younger Dryas (GS-1) transition. After 100–200 years, CO2 concentration started to gradually increase to 270–290 ppmv at the end of the Younger Dryas stadial (GS-1). CO2 concentrations were relatively stable during the early Holocene, except for a short-lived period of lower (240–250 ppmv) values c. 11 350–11 200 cal yr BP. This Late-glacial and early Holocene CO2 evolution partly resembles previous stomatal-based CO2 reconstructions, and the overall trend is almost identical to that seen in ice-core records. The amplitude of change is, however, markedly higher in the Swedish stomatal-based record compared to the ice cores. This difference may partly be accounted for by the inherent smoothing of ice-core CO2 records caused by diffusion, but a major part of the difference in amplitude between ice-core and stomatal-based records still remains to be explained. Based on our reconstruction, atmospheric CO2 may have played an important role in climate dynamics during the last deglaciation.
Keywords: CO2; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен